Pemanfaatan Limbah Karet Bekas sebagai Agregat Kasar pada Pembuatan Beton Berkelanjutan - Priyanitama, Muhammad Ikhsan; Hasibuan, Samsul Abdul Rahman Sidik (Sultra Civil Engineering Journal (SCiEJ), 2025)
Concrete is a primary material in construction with significant environmental impacts, especially due to the use of cement and natural aggregates. One alternative to reduce this impact is by utilizing waste rubber as a partial replacement for coarse aggregate in concrete production. This study aims to evaluate the effect of adding waste rubber on the mechanical properties of concrete, particularly compressive strength and workability. In this study, waste rubber was added at 5%, 10%, and 15% of the total weight of coarse aggregate. Slump tests were conducted to measure the workability of the concrete, while compressive strength tests were carried out at 14 and 28 days to evaluate the development of the concrete’s strength. The results of the study show that concrete with added waste rubber exhibited better workability, indicated by higher slump values compared to normal concrete. Although the compressive strength of concrete with waste rubber was slightly lower at 14 days, at 28 days, the strength significantly increased. This study suggests that waste rubber can be used as an alternative coarse aggregate in concrete, considering the appropriate proportion to achieve a balance between the strength of the concrete and environmental sustainability.